Relationship between Fusobacterium nucleatum and antitumor immunity in colorectal cancer liver metastasis. Issue 11 (23rd September 2021) - Sakamoto, Yuki; Mima, Kosuke; Ishimoto, Takatsugu; Ogata, Yoko; Imai, Katsunori; Miyamoto, Yuji; Akiyama, Takahiko; Daitoku, Nobuya; Hiyoshi, Yukiharu; Iwatsuki, Masaaki; Baba, Yoshifumi; Iwagami, Shiro; et al.
Abstract: Fusobacterium nucleatum has been detected in 8%‐13% of human colorectal cancer, and shown to inhibit immune responses against primary colorectal tumors in animal models. Thus, we hypothesized that the presence of F . nucleatum might be associated with reduced T cell density in colorectal cancer liver metastases (CRLM). We quantified F . nucleatum DNA in 181 CRLM specimens using quantitative PCR assay. The densities of CD8 + T cells, CD33 + cells (marker for myeloid‐derived suppressor cells [MDSCs]), and CD163 + cells (marker for tumor‐associated macrophages [TAMs]) in CRLM tissue were determined by immunohistochemical staining. Fusobacterium nucleatum was detected in eight (4.4%) of 181 CRLM specimens. Compared with F . nucleatum ‐negative CRLM, F . nucleatum ‐positive CRLM showed significantly lower density of CD8 + T cells ( P  = .033) and higher density of MDSCs ( P  = .001). The association of F. nucleatum with the density of TAMs was not statistically significant ( P  = .70). The presence of F . nucleatum is associated with a lower density of CD8 + T cells and a higher density of MDSCs in CRLM tissue. Upon validation, our findings could provide insights to develop strategies that involve targeting microbiota and immune cells for the prevention and treatment of CRLM. Abstract : Fusobacterium nucleatum was detected in eight (4.4%) of 181 colorectal cancer liver metastasis tissue. We found that the presence of F. nucleatum was associated with lower CD8 + T cell density and greater densities of both myeloid‐derived suppressor cells and tumor‐associated macrophages.